Clinical practice guidelines for the management of adult diffuse gliomas - Jiang, Tao; Nam, Do-Hyun; Ram, Zvi; Poon, Wai-sang; Wang, Jiguang; Boldbaatar, Damdindorj; Mao, Ying; Ma, Wenbin; Mao, Qing; You, Yongping; Jiang, Chuanlu; Yang, Xuejun; et al. (Cancer letters, 2021)
To follow the revision of the fourth edition of WHO classification and the recent progress on the management of diffuse gliomas, the joint guideline committee of Chinese Glioma Cooperative Group (CGCG), Society for Neuro‐Oncology of China (SNO-China) and Chinese Brain Cancer Association (CBCA) updated the clinical practice guideline. It provides recommendations for diagnostic and management decisions, and for limiting unnecessary treatments and cost. The recommendations focus on molecular and pathological diagnostics, and the main treatment modalities of surgery, radiotherapy, and chemotherapy. In this guideline, we also integrated the results of some clinical trials of immune therapies and target therapies, which we think are ongoing future directions. The guideline should serve as an application for all professionals involved in the management of patients with adult diffuse glioma and also a source of knowledge for insurance companies and other institutions involved in the cost regulation of cancer care in China and other countries. •The guideline provides diagnostic and management recommendations for diffuse gliomas.•The guideline focuses on molecular diagnostics, and the main treatment modalities.•The guideline includes clinical trials of immune therapies and target therapies.•The guideline should serve as an application for all medical professionals.